2013
DOI: 10.1590/s0100-83582013000300012
|View full text |Cite
|
Sign up to set email alerts
|

Análise de crescimento de erva-de-touro em competição com soja cultivada sob deficiência hídrica

Abstract: Devido à ausência na caracterização competitiva de espécies de plantas daninhas e suas habilidades sob condições edafoclimáticas desfavoráveis, avaliou-se o potencial de competição de Tridax procumbens em meio à cultura da soja. O cultivo foi realizado em condições controladas, em câmara de crescimento, utilizando-se o sistema de séries substitutivas, o qual abrangeu os monocultivos das espécies e a sua competição, com suprimento adequado de água e sob condições de deficiência hídrica temporária. Avaliaram-se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The analysis of coatbutton (Tridax procumbens L.) growth, a C 3 species competing with soybean, showed that the crop not only had higher height, leaf area and shoot dry matter than the weed even when undergoing temporary water deficit, but also exhibited high intraspecific competition (Vivian et al, 2013).…”
Section: /9mentioning
confidence: 99%
“…The analysis of coatbutton (Tridax procumbens L.) growth, a C 3 species competing with soybean, showed that the crop not only had higher height, leaf area and shoot dry matter than the weed even when undergoing temporary water deficit, but also exhibited high intraspecific competition (Vivian et al, 2013).…”
Section: /9mentioning
confidence: 99%